2009
DOI: 10.1007/s00445-009-0297-3
|View full text |Cite
|
Sign up to set email alerts
|

Lower-crustal earthquakes caused by magma movement beneath Askja volcano on the north Iceland rift

Abstract: The lower crust of magmatically active rifts is usually too hot and ductile to allow seismicity. The Icelandic mid-Atlantic rift is characterized by high heat flow, abundant magmatism generating up to 25-30 km thick crust, and seismicity within the upper 8 km of the crust. In a 20-seismometer survey in July-August 2006 within the northern rift zone around the Askja volcano we recorded~1700 upper-crustal earthquakes cutting off at 7-8 km depth, marking the brittle-ductile boundary. Unexpectedly, we discovered 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 37 publications
6
85
0
Order By: Relevance
“…This cluster at Öskjuvatn has been seen in seismic data since 1975 (Einarsson, 1991;Jakobsdóttir, 2008;Greenfield and White, 2015) and was hypothesised to be caused by hydrothermal circulation above a shallow magma body (Soosalu et al, 2010) or by thermal cracking and heat extraction in the crust 30 (Einarsson, 1991 Relocation of 86 earthquakes in this southeastern hydrothermal area at lake Öskjuvatn showed that the events are concentrated at depths between 2-4 km b.s.l. (Greenfield et al, in press).…”
Section: Seismicitymentioning
confidence: 89%
See 2 more Smart Citations
“…This cluster at Öskjuvatn has been seen in seismic data since 1975 (Einarsson, 1991;Jakobsdóttir, 2008;Greenfield and White, 2015) and was hypothesised to be caused by hydrothermal circulation above a shallow magma body (Soosalu et al, 2010) or by thermal cracking and heat extraction in the crust 30 (Einarsson, 1991 Relocation of 86 earthquakes in this southeastern hydrothermal area at lake Öskjuvatn showed that the events are concentrated at depths between 2-4 km b.s.l. (Greenfield et al, in press).…”
Section: Seismicitymentioning
confidence: 89%
“…In the region of the Askja volcanic system, earthquakes occur at two levels in the crust, as shallow crustal seismicity between the surface and mostly 5 km depth, and as deep seismicity in the ductile lower crust at depths of 10-35 km, with magnitudes of usually M L <3 (Jakobsdóttir et al, 2002;Soosalu et al, 2010;Greenfield et al, 2015). 20…”
Section: Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although eruptions occurred in Askja between 1921 and 1929 and in 1961, the most recent episode of major rifting occurred in 1874-1876 81 . Current deformation at Askja has been well documented by GPS, InSAR and levelling data [82][83][84][85][86] , and seismicity has been mapped using a dense local network 80,87,88 . The zones of horizontal and vertical strain accumulation seem to act on different length scales: extension, at the expected full plate-spreading rate, is distributed over a zone ~80 km wide, whereas rift-axis subsidence is concentrated within the central ~20-km-wide zone of faulting and fissures (Fig.…”
Section: Activity Between and Preceding Major Episodesmentioning
confidence: 99%
“…Recent deployments of dense seismic arrays around Askja have detected several clusters of micro-earthquake activity in the lower crust, which is normally ductile 87,88 . These have been interpreted as areas where high rates of melt movement generate strain rates that are sufficient to cause brittle failure.…”
Section: Activity Between and Preceding Major Episodesmentioning
confidence: 99%